Periodontal instrument sharpness assessment - Yaacob, Munirah (Centre for Professional Development, 2022)
The periodontal disease affect 20-50% of the different populations worldwide. Local factors like plaque biofilm and calculus are the main factors for periodontal disease initiation and progression. Therefore, the removal of these local factors to obtain a clean and smooth root surface is obligatory to restore and sustain the periodontal health. The periodontal instrument used for scaling and sub-gingival debridement includes ultrasonic scalers, manual scalers, and curettes. The instruments such as manual scalers and curettes have a cutting blade that can become easily blunted and require sharpening regularly. A sharp cutting blade is essential to ensure the quality of periodontal instrumentation, improve patient comfort, and reduce operator fatigue. Furthermore, it enhances the tactile sensitivity, easily detect, and removes calculus deposit efficiently. It also reduces the amount of lateral pressure and stroke to perform the desired function. Therefore, periodic checking of the instruments' conditions is critical to ensure their sharpness and effective periodontal treatment. There are four methods to determine the sharpness of an instrument.